'Missing Presumed': computer games and digital adventures in the Colin Smythe/Terry Pratchett Collection. Issue 3 (2nd September 2019) - Castrillo, Maria
ABSTRACT: This essay explores the intersections between literature and new media through the lens of the Discworld computer games based on Sir Terry Pratchett's novels. Although Pratchett was one of the twentieth century's most successful authors in the English language, he has been largely absent from literary criticism, chiefly because he was and continues to be perceived as a popular author, a writer for the masses. The popularity of his Discworld series of novels led computer game developers to adapt them to new media in the 1980s and 1990s. The Colin Smythe/Terry Pratchett collection at Senate House Library, University of London, provides a treasure trove of information to understand this aspect of Pratchett's vast literary and publishing output as a result of the survival of invaluable analogue peripheral records, visual and printed sources which document the creative process and Pratchett's input. The essay argues that although these digital objects have been largely treated as physical objects and have been mostly retained for their artefactual and anecdotal value, the existence of analogue sources provides a unique opportunity to explore them in more detail, taking into account the historical, social and cultural context that enabled their creation to inform their future digital preservation.